2014
DOI: 10.1177/1932296813516958
|View full text |Cite
|
Sign up to set email alerts
|

Biosimilar Insulins

Abstract: Until now most of the insulin used in developed countries has been manufactured and distributed by a small number of multinational companies. Beyond the established insulin manufacturers, a number of new players have developed insulin manufacturing capacities based on modern biotechnological methods. Because the patents for many of the approved insulin formulations have expired or are going to expire soon, these not yet established companies are increasingly interested in seeking market approval for their insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Only now, with intellectual property (i.e., patents) for many insulin analogues having recently expired or expiring soon [19], have biosimilar insulin analogues been marketed. However, there is still no inexpensive supply of insulin biosimilars for people living with diabetes in North America, and Americans are paying a steep price for the 'continued rejuvenation' of this medicine [10].…”
Section: Insulin Is a Prohibitively Expensive Essential Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…Only now, with intellectual property (i.e., patents) for many insulin analogues having recently expired or expiring soon [19], have biosimilar insulin analogues been marketed. However, there is still no inexpensive supply of insulin biosimilars for people living with diabetes in North America, and Americans are paying a steep price for the 'continued rejuvenation' of this medicine [10].…”
Section: Insulin Is a Prohibitively Expensive Essential Medicinementioning
confidence: 99%
“…Meanwhile, at least 11 insulin biosimilars are marketed (under less stringent regulatory frameworks) at considerably lower price points in China, India, Mexico, Pakistan, Peru, and Thailand [20]. Studies comparing a handful of these biosimilars to innovator insulins showed no meaningful differences [19,20].…”
Section: Insulin Is a Prohibitively Expensive Essential Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…2). The manufacturing processes are proprietary, and different manufacturers use different processes, increasing the potential for structural differences between biologicals 9, 10.…”
Section: Manufacture Of Biological Drugs As Source Of Variabilitymentioning
confidence: 99%
“…It is evident then, that as more biosimilar insulins come to market, independent studies of batch‐to‐batch variability, and if possible clinical correlates, are desirable 10, 12.…”
Section: Manufacturing and Batch‐to‐batch Variabilitymentioning
confidence: 99%